Project management : tools and techniques for today's ILS professional - Allan, Barbara, 1954- (London : Facet, 2004)
Supported by practical case studies drawn from a wide range of ILS organizations at local, regional, national and international levels, this text explores tried and tested methods and techniques for managing projects.
pt. 1. Introduction -- 1. Introduction -- pt. 2. project life cycle, systems and processes -- 2. project life cycle and project analysis -- 3. Planning the project -- 4. Implementation -- 5. Evaluation and dissemination -- 6. money side of projects -- 7. Using ICT to support the project -- pt. 3. Projects and people -- 8. people side of projects -- 9. Working in partnership -- 10. Working on projects -- 11. Project management skills and training -- App. A. language of funding.
Includes bibliographical references and index.
NLJCols20082021
Keywords: Project management; Library administration; Library Administration; Biblioth eques -- Administration; Gestion de projets; Library administration; Project management; Projectmanagement; Informatiecentra; Bibliotheekdiensten